Portuguese local government’s typology of tourism policy tools: how many clusters? - Costa, Cláudia S. (2018)
The evolution of Public Policy, in general, and tools approach, in particular, has recognized a wide range of policy tools, beyond the traditional direct provision. In fact, such development has enabled the design of several public policy typologies, in specific the Weimer and Vining’s typology, which is one of the most important and comprehensive in classifying governments interventions to solve market failures. Based on market failures theory and the tools approach, this research extends their analysis to the context of tourism providing a broader typology of policy tools specifically aimed at tourism policy at the local level. In this sense, the design a typology of tourism policy tools represents the main goal and the original contribution of this research. Given this goal, we defined a multi-methods research plan, using questionnaires and interviews as data collection techniques. Particularly, based on information gathered from interviews, we created and apply a questionnaire to the 308 Portuguese municipalities. This empirical analysis uses a representative sample of 214 Portuguese municipalities and the cluster analysis technique to classify the tourism policy tools used by Portuguese municipalities. The main results suggest a strong alignment with Weimer and Vining’s typology but at the same time the existence of particular situations in Portuguese municipalities demanding the extension of this typology. Besides the many policy options, the intervention by Portuguese municipalities in tourism relies predominantly in the use of direct provision. For many municipalities, the direct provision cluster represents the main set of policy tools employed to solve tourism market failures.